PENGEMBANGAN MEDIA PEMBELAJARAN MATA KULIAH EKOLOGI HEWAN BERBASIS MACROMEDIA FLASH 8 MATERI ADAPTASI HEWAN - Liline, Sintje; Kubangun, Muhammad Tarmizi; Heremba, Wa Nurul Mutmainah J (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: The learning process of the Animal Ecology course for Biology Education study program students of the Pattimura University Ambon University of Biology is carried out conventionally and uses media in the form of Microsoft power points so that multimedia-based learning media development is carried out using Macromedia flash 8 software, on animal adaptation material. The purpose of this study was to determine the product development of learning media for Animal Ecology courses based on Macromedia flash professional 8 for students of the Biology Education Study Program, FKIP, Pattimura University, Ambon. Methods: This research is development research using the 4D development model (proposed by Thiagarajan et al., 1974. The 4-D development model consists of 4 stages of development known as define, design, develop and disseminate. The development of learning media is limited to the development or development stage. This research was conducted in July-December 2020 and was carried out in the Biology Education Study Program FKIP Pattimura University Result: the validation data analysis by the material expert team was 88.95% (very good) and the media expert was 88.33% (very good). The results of data analysis on product testing activities for students in small groups obtained a value of 81.16% (good) and product testing for students in large groups obtained a value of 85.28% (very good). Conclusion: Learning media based on Macromedia flash 8 for animal adaptation material in animal ecology courses can be used as a learning medium because it is very good